2021
DOI: 10.1002/emp2.12619
|View full text |Cite
|
Sign up to set email alerts
|

Heal the Healers: A pilot study evaluating the feasibility, acceptability, and exploratory efficacy of a Transcendental Meditation intervention for emergency clinicians during the coronavirus disease 2019 pandemic

Abstract: Objective Emergency clinicians face elevated rates of burnout that result in poor outcomes for clinicians, patients, and health systems. The objective of this single‐arm pilot study was to evaluate the feasibility of a Transcendental Meditation (TM) intervention for emergency clinicians during the coronavirus disease 2019 (COVID‐19) pandemic and to explore the potential effectiveness in improving burnout, sleep, and psychological health. Methods Emergency clinicians (physicians, nurses, and physician‐assistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…Therefore, it is important to pay attention to the well-being of all nurses, including leaders, particularly as we view the lingering results of the pandemic on key workforce outcomes. Several publications describe interventional studies that may improve nurse well-being such as education/ self-reflection (Sawyer et al, 2022), resilience retreats (Cunningham & Çayir, 2021), text messaging (Kelly et al 2021), wellness partners (Teall & Melnyk, 2021) and transcendental meditation (Azizoddin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to pay attention to the well-being of all nurses, including leaders, particularly as we view the lingering results of the pandemic on key workforce outcomes. Several publications describe interventional studies that may improve nurse well-being such as education/ self-reflection (Sawyer et al, 2022), resilience retreats (Cunningham & Çayir, 2021), text messaging (Kelly et al 2021), wellness partners (Teall & Melnyk, 2021) and transcendental meditation (Azizoddin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to the TM intervention, as assessed by a TM teacher, was defined as (1) treatment session adherence, comprising attendance at at least 6 of 8 sessions (75%), and (2) TM home practice adherence, comprising meditation at least once per day on average. 30,31…”
Section: Jama Network Open | Occupational Healthmentioning
confidence: 99%
“…[ 44 ] Azizoddin et al observed a significant reduction in stress- induced psychological symptoms of emergency workers during the SARS-CoV 2 pandemic after a transcendental meditation intervention. [ 45 ]…”
Section: Resultsmentioning
confidence: 99%